Can decentralized science help tackle the deterioration in working conditions in academia? - Sicard, François (Frontiers in Blockchain, 2022)
Academic staff’s working conditions have been deteriorating for years. In particular, the reduced availability of both research funding and permanent research positions has continuously led to insidious competition and intense stress among academics. Whereas governing bodies have made significant attempts to narrow pervasive social inequalities in the distribution of research funding within the scientific community, they have not truly taken into account the importance of the academics’ overall well-being in the development of more sustainable financing of academic researchers. This originates not only from the complexity to develop comprehensive models reflecting staff’s overall well-being in the academic environment, but also from the limited access to reliable and immutable data that transparently account for the staff’s direct experience. In this context, blockchain technology can push further the use of more transparent survey data collection and record-keeping that can help mitigate the systematic bias inherent to the centralized nature of traditional auditing. We discuss how research institutions and governing bodies can build on blockchain technology and the early momentum generated by the decentralized science (DeSci) movement to implement the future-proof research funding chain that values overall well-being across academia in a transparent and coordinated way.